DEVELOPMENT OF DIGITAL COMPETENCE AMONG RESEARCHERS AND EDUCATIONAL PROFESSIONALS THROUGH ELECTRONIC SOCIAL NETWORKS - Yaskova, Nataliya; Labzhynskyi, Yuriy (Physical and Mathematical Education, 2024)
Formulation of the problem. In today’s information society, the importance of digital competence for researchers and academic educators is growing. As digital technologies continuously evolve, professionals are compelled to adapt to new tools and platforms. However, there exists a significant gap between the need for digital skills and their actual levels among this category of professionals. Adapting to various formats of learning and communication (online courses, webinars, forums) is a crucial component of modern digital competence. Electronic social networks, as platforms for professional communication, knowledge exchange, and collaboration, can serve as powerful tools for developing these competencies. At the same time, a lack of awareness regarding the potential uses of electronic social networks may hinder their effective application for professional growth. Many researchers and academic educators do not know how to optimally utilize these platforms for knowledge sharing, networking, and collaboration with colleagues. This underscores the need for a systematic approach to developing digital competencies, which includes training, support, and resource provision. Therefore, exploring the opportunities of electronic social networks as tools for developing digital competencies is a relevant and important step toward bridging the identified gap. Materials and methods. A combination of methods was employed for the research, including analysis, synthesis, comparison, and generalization to study both foreign and domestic scientific literature regarding the content of key concepts; comparison and examination of pedagogical experiences related to the research problem; and terminological analysis to clarify the research vocabulary. Results. The application of electronic social networks has a positive impact on the development of competencies among researchers and educational professionals. Conclusions. Developing digital competence is essential for researchers and educational professionals, as contemporary research and educational processes increasingly rely on technology and online tools. Social networks provide opportunities for professional development, knowledge sharing, collaboration, and networking, which foster the formation of digital competencies. The use of social networks can positively influence the visibility of scientific achievements, facilitating access to new information resources and colleagues, thereby contributing to the advancement of science. It is recommended to implement training sessions and seminars focusing on the practical use of electronic social networks, as well as to create supportive online communities for knowledge exchange.